Hubungan Antara Gaya Kepemimpinan, Manajemen Sumber Daya Manusia Dengan Kualitas Kinerja Pegawai UPT Samsat Kota Pinang - Seniman Seniman; Rajab Lubis; Sjahril Effendy (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
The purpose of this article is to find out whether there is a relationship between leadership style, human resource management and the quality of performance of the employees of UPT Samsat Kota Pinang. The research method used is descriptive correlative with a correlative study pattern by choosing the position of the research variables in two groups, namely the independent variable and the dependent variable. The research population is the employees of UPT Samsat Kota Pinang who have a minimum working period of 5 years. The sampling technique used is Proportional Random Sampling technique with the number of selected samples as many as 37 people. This article is expected to contribute to the development of knowledge in the field of Industrial and Organizational Psychology. The results of this study can be used for the purposes of developing knowledge both conceptually and practically.